2013
DOI: 10.1021/ol400348a
|View full text |Cite
|
Sign up to set email alerts
|

Amomaxins A and B, Two Unprecedented Rearranged Labdane Norditerpenoids with a Nine-Membered Ring from Amomum maximum

Abstract: Amomaxins A (1) and B (2), featuring an unprecedented rearranged labdane norditerpene skeleton with a nine-membered ring, along with their biosynthetic related known compound isocoronarin D (3) were isolated from the roots of Amomum maximum. Their structures with absolute configurations were determined by spectroscopic data, CD experimentation, and single-crystal X-ray diffraction. Compound 2 showed an inhibitory effect on nitric oxide (NO) production in lipopolysaccharide-induced RAW264.7 macrophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…An investigation has shown that the extract of A. maximum acts as anthelmintic against the cestode, Raillietina echinobothrida (Chetia et al 2014). Phytochemical studies revealed the characterisation of labdane triterpenoids, diterpenes (Luo et al 2014), amomaxins A and B as well as isocoronarin (Yin et al 2013) from the plant. No record of the composition of its essential oil could be found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…An investigation has shown that the extract of A. maximum acts as anthelmintic against the cestode, Raillietina echinobothrida (Chetia et al 2014). Phytochemical studies revealed the characterisation of labdane triterpenoids, diterpenes (Luo et al 2014), amomaxins A and B as well as isocoronarin (Yin et al 2013) from the plant. No record of the composition of its essential oil could be found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Fig. 8 , the pathways of 1 – 8 originating from cadalenequinone, which was considered as the biosynthetic monomeric precursor of involucratustones A–C 4 , were presumed, in which nucleophilic addition 9 26 , S N 2 nucleophilic displacement 27 , [3 + 3] benzannulation 28 , oxidative cleavage 29 , decarboxylation 30 31 , oxidative phenol coupling 32 were included.…”
Section: Resultsmentioning
confidence: 99%
“…In the Fig. 8 , it is revealed that the formation of nor-cadinane-dimer 4 is attributed to the decarboxylation reaction, which is the most common biogenetic pathway to form norterpenoids 2 9 33 34 35 . However, interesting, different from the most norterpeniods, the carbon skeletons of dinor-cadinane-dimers 5 and 6 , dodecanor-cadinane-dimer 7 , and tetradecanor-cadinane-dimer 8 were speculated to be produced by the key oxidative cleavage reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AMS-19 to AMS-21 were combined and subjected to prep-HPLC with MeOH-H 2 O (45 : 55, v/v, 10 mL/ min) to give 1 (6 mg Nitric Oxide (NO) Production Bioassay The protocol for NO production bioassays was provided in previously published papers. 30) N-Monomethyl-L-arginine was used as the positive control. All experiments were performed in three replicates.…”
Section: Experimental General Experimental Procedures Optical Rotationsmentioning
confidence: 99%